Features of legal protection of objects of copyright according to legislation of Ukraine - Сопілко, Ірина Миколаївна; Пономаренко, Олександр Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In this article, the authors examines features of providing the legal protection of copyright in accordance with existing legislation. At the same time, in the process of research focus attention on a faults of current legislation, and form the main directions of improvement of legislation in accordance with the international legal standards in the field of copyright protection